Effects of mannanoligosaccharide and sodium chlorate on growth performance of nursery pigs during an acute enteric disease challenge with Salmonella enterica serotype typhimurium - T E Burkey; Jerome C Nietfeld; B J Johnson; J Ernest Minton; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
A 28-day experiment was conducted to compare the effects of feeding mannanoligosaccharides (mannan) and sodium chlorate (chlorate) to weanling pigs as a possible substitute for the commonly used antimicrobialcarbadox. Pigs were fed experimental diets for 2 wk, then challenged orally with Salmonella enterica serotype typhimurium to establish enteric disease. Average daily gain and ADFI were greater for pigs fed carbadox than all other treatments in the 2 wk following infection. During the first week after infection, pigs fed chlorate had greater G/F than control pigs, and pigs fed mannan tended to have greater G/F than control pigs. There were no differences in feed efficiency among treatments during the second week following infection.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Mannanoligosaccharides; Sodium Chlorate; Antimicrobials; Weanling pigs; Swine